Efektivitas Program Motekar dalam Mengurangi Angka Perceraian di Jawa Barat: The Effectiveness of the Motekar Program in Reducing Divorce Rates in West Java - Septiani, Wanda Hamidah; Nurhadi, Nurhadi; Liestyasari, Siany Indria (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2024)
This study aims to assess the effectiveness of the Family Resilience Motivator Program (Motekar) in addressing the high rates of divorce in West Java Province, primarily driven by ongoing disputes and forced marriages. Instituted by Regional Regulation No. 9 of 2014, this program endeavors to enhance family resilience through community empowerment and social interventions. Utilizing a descriptive qualitative methodology, this research investigates the impact of the Motekar facilitators in Banjar City. The findings suggest that although the program holds promise in mitigating family conflicts and reducing divorce rates, it faces significant challenges, including insufficient numbers of facilitators and limited resources. Therefore, this study recommends an increase in human and financial resources, as well as strengthened collaborations among stakeholders, to bolster the program's implementation and achieve sustainable family stability. The research highlights the crucial role of community-based interventions in promoting family resilience amid complex social challenges. Abstrak Penelitian ini bertujuan untuk mengkaji efektivitas Program Motivator Ketahanan Keluarga (Motekar) dalam mengatasi tingginya angka perceraian di Provinsi Jawa Barat. Berdasarkan Peraturan Daerah Nomor 9 Tahun 2014, program ini mengusahakan peningkatan ketahanan keluarga melalui pemberdayaan komunitas dan intervensi sosial. Metode kualitatif deskriptif digunakan dalam penelitian ini untuk menggali lebih dalam efektivitas kader Motekar di Kota Banjar. Hasil penelitian menunjukkan bahwa, meskipun program tersebut menjanjikan dalam mengurangi konflik keluarga dan perceraian, ada hambatan signifikan yang ditemui, termasuk kekurangan jumlah kader dan keterbatasan sumber daya. Oleh karena itu, direkomendasikan peningkatan sumber daya manusia dan dana operasional, serta penguatan kerja sama antar stakeholder untuk memperkuat implementasi program dan mencapai stabilitas keluarga yang berkelanjutan. Studi ini menegaskan pentingnya peran intervensi berbasis komunitas dalam mempromosikan ketahanan keluarga di tengah tantangan sosial yang kompleks.